The Role of Free Tissue Transfer in Posterior Neck Reconstruction - Yanko-Arzi, Ravit; Gur, Eyal; Margulis, Alexander; Bickels, Jacob; Dadia, Shlomo; Gortzak, Yair; Zaretski, Arik (Journal of Reconstructive Microsurgery, 2014)
Reconstruction of the posterior neck is one of the rarer procedures performed by plastic surgeons; we used free flaps for the closure of defects in this area in six cases over the past 4 years. Six patients were located requiring posterior neck reconstruction between the years 2007 and 2013. Five of these patients required reconstruction due to oncologic resections, while one underwent serial removal of a giant congenital nevus. Five of these reconstructions involved the use of a free anterolateral thigh/vastus lateralis flap, and the sixth received a pre-expanded deep inferior epigastric perforator flap. Satisfactory dorsal neck reconstruction was achieved with the free flap approach: it produced excellent healing, contour and coverage of hardware. There was only one early minor complication, allowing early return to daily activities and continuation of planned oncologic treatment. Free flap reconstruction of the posterior neck area is a safe and relatively rapidly performed procedure that yields good results both functionally and aesthetically. In this article, we review the literature on the options available for reconstruction of the posterior neck, describe our surgical experience in such cases, and suggest an algorithm to guide in choosing the optimal approach for a given patient.
Keywords: posterior neck; free flap; anterolateral thigh